EVALUATION OF ENERGY LOSSES IN TRACTION NETWORK OF TRUNK RAILWAYS - Kuznietsov, V. H.; Mytsko, R. S.; Bosyi, D. O. (Science and Transport Progress, 2006)
An indirect method of electric power losses determination in catenary has been examined. An example of solving such task with the help of specialized imitation model has been given and results of statistic analysis have been presented. Possible ways of using the obtained results have been exemplified.